Descriptive assessment of problem behavior during transitions of children with intellectual and developmental disabilities. Issue 1 (23rd January 2018) - Castillo, Mariana I.; Clark, Daniel R.; Schaller, Erin A.; Donaldson, Jeanne M.; DeLeon, Iser G.; Kahng, SungWoo
Abstract : Transitions from one activity to another may evoke problem behavior from individuals with intellectual disabilities. One explanation for the occurrence of problem behavior could be the change in relative densities of reinforcement between the two activities. We conducted a descriptive assessment of problem behavior with four children during transitions to and from several different contexts. We observed that, in most cases, the probability of problem behavior was greater during a transition to an activity with a lower density of reinforcement than during a transition to an activity with a higher density of reinforcement. We discuss our findings in terms of problem behavior associated with transitions in activities with different reinforcer densities, as well as the possibility that the problem behavior may be associated with shifts in motivating operations.